A Unique Case of Lemierre Syndrome Associated with Thrombophilia in an Adult and the Role of Anticoagulation - Pradeep H. Lakshminarayana; Matthew E. Woodske (Case Reports in Medicine)
Acute septic thrombophlebitis of the internal jugular vein (IJV), better known as Lemierre syndrome, is a rare entity which poses several challenges in management. Treatment involves prompt use of intravenous antibiotics over a prolonged period of time, typically 6–8 weeks. The use of anticoagulation is controversial, but indicated for some. We describe the first reported case of Lemierre syndrome associated with a hypercoagulable state in an adult. We propose that all patients with Lemierre syndrome should be evaluated for hypercoagulable states and that the indications for anticoagulation in Lemierre syndrome are (1) propagation or nonresolution of IJV thrombus despite antibiotics and (2) identification of a hypercoagulable state, as in our case.